The effects of low-ratio n-6/n-3 PUFA on biomarkers of inflammation: a systematic review and meta-analysis. Issue 1 (24th November 2020) - Wei, Yali; Meng, Yan; Li, Na; Wang, Qian; Chen, Liyong
Abstract : The purpose of the systematic review and meta-analysis was to determine if low-ratio n-6/n-3 long-chain polyunsaturated fatty acid (PUFA) supplementation affects serum inflammation markers based on current studies. Abstract : Objective : The purpose of the systematic review and meta-analysis was to determine if low-ratio n-6/n-3 long-chain polyunsaturated fatty acid (PUFA) supplementation affects serum inflammation markers based on the current studies. Methods : PubMed, Embase and The Cochrane library databases were systematically searched to find randomized controlled trials (RCTs) on the effect of low-ratio n-6/n-3 PUFA intervention on inflammation markers up to July 2020. Data were pooled using standardized mean difference (SMD) and 95% confidence intervals (95% CI), with P value ≦ 0.05 as statistical significance. Results : Thirty-one RCTs were included in the meta-analysis. The analysis indicated that increasing low-ratio n-6/n-3 PUFA supplementation decreased the level of tumor necrosis factor-α (TNF-α) (SMD = −0.270; 95% CI: −0.433, −0.106; P = 0.001) and interleukin 6 (IL-6) (SMD = −0.153; 95% CI: −0.260, −0.045; P = 0.005). There were no significant effects on C-reactive protein (CRP) (SMD = −0.027; 95% CI: −0.189: 0.135; P = 0.741). Subgroup analysis indicated that there was a significant reduction in TNF-α serum concentration in subjects from Asia (SMD: −0.367; 95% CI: −0.579, −0.155; P = 0.001) and in subjects with diseases (SMD: −0.281; 95% CI: −0.436, −0.127; P < 0.001). In the subgroup of the n-6/n-3 ratio ≦5, low-ratio n-6/n-3 PUFA supplementation could decrease the level of TNF-α (SMD: −0.335; 95% CI: −0.552, −0.119; P = 0.002). Serum IL-6 decreased significantly in patients from the Europe subgroup (SMD: −0.451; 95% CI: −0.688, −0.214; P < 0.001), but not in Asia (SMD: −0.034; 95% CI: −0.226, 0.157; P = 0.724), North America (SMD: −0.115; 95% CI: −0.274, 0.044; P = 0.157) and Oceania (SMD: 0.142; 95% CI: −0.557, 0.842; P = 0.690). Conclusion : Low-ratio n-6/n-3 PUFA supplementation could decrease significantly the concentration of serum TNF-α and IL-6, but not decrease CRP concentration.